Experimental risk assessment for chikungunya virus transmission based on vector competence, distribution and temperature suitability in Europe, 2018 - Heitmann, Anna; Jansen, Stephanie; Lühken, Renke; Helms, Michelle; Pluskota, Björn; Becker, Norbert; Kuhn, Carola; Schmidt-Chanasit, Jonas; Tannich, Egbert (Eurosurveillance, 2018)
Background Over the last decade, the abundant distribution of the Asian tiger mosquito Aedes albopictus in southern Europe and the import of chikungunya virus (CHIKV) by infected travellers has resulted in at least five local outbreaks of chikungunya fever in France and Italy. Considering the ongoing spread of Ae. albopictus to central Europe, we performed an analysis of the Europe-wide spatial risk of CHIKV transmission under different temperature conditions. Methods:Ae. albopictus specimens from Germany and Italy were orally infected with CHIKV from an outbreak in France and kept for two weeks at 18 °C, 21 °C or 24 °C. A salivation assay was conducted to detect infectious CHIKV. Results: Analyses of mosquito saliva for infectious virus particles demonstrated transmission rates (TRs) of > 35%. Highest TRs of 50% for the mosquito population from Germany were detected at 18 °C, while the Italian population had highest TRs of 63% at 18 °C and 21 °C, respectively. Temperature data indicated a potential risk of CHIKV transmission for extended durations, i.e. sufficiently long time periods allowing extrinsic incubation of the virus. This was shown for areas already colonised by Ae. albopictus, as well as for large parts of central Europe that are not colonised. Conclusion: The current risk of CHIKV transmission in Europe is not primarily restricted by temperature, which allows extrinsic incubation of the virus, but rather by the vector distribution. Accordingly, all European countries with established populations of Ae. albopictus should implement respective entomological surveillance and monitoring systems, as basis for suitable control measures.
Gesehen am 23.09.2019